Unpacking organizational awareness: scale development and empirical examinations in the context of distributed knowledge sharing. Issue 1 (2nd January 2019) - Kim, Heewon; Gibbs, Jennifer L.; Scott, Craig R.
ABSTRACT: Organizational awareness has been viewed as a critical factor in facilitating collaboration and knowledge sharing, particularly among dispersed workers. Drawing on the findings of three studies, we disentangle the complex nature of organizational awareness, with a focus on its role in distributed knowledge sharing. First, we developed and validated an organizational awareness scale to investigate organizational awareness as a multidimensional construct that consists of availability awareness, task awareness, and social awareness. Second, employing the scale, we examined the relationships among organizational awareness, the use of enterprise social media (ESM), and knowledge acquisition in a global organization. The results of structural equation modeling demonstrated that ESM use was positively linked to distributed workers' task awareness, which subsequently enhanced knowledge acquisition. Lastly, interview findings revealed how task awareness was cultivated by ESM use. Synthesizing the findings, we offer detailed accounts of organizational awareness and its relationships with dispersed workers' knowledge sharing practice.